Self-Medication Practices among University Students during the COVID-19 Pandemic - Halim, Steven Victoria; Kumala, Stefany Marcellia; Sharifah, Fatichatus; Setiawan, Eko; Setiadi, Antonius Adji Prayitno (Sciences of Pharmacy, 2025)
Self-medication is a treatment effort often undertaken by students, especially when the burden on healthcare services increases due to the coronavirus disease 2019 (COVID-19) pandemic. Nevertheless, up to five years after the onset of the global pandemic caused by the SARS-CoV-2 virus, no empirical evidence has been found to elucidate the self-medication practice among students in Indonesia. This observational study with a cross-sectional design aimed to identify students' self-medication practices at a university during the second wave of the COVID-19 pandemic. The research data was collected online using a questionnaire (Google Form). The questionnaire used consisted of two parts: student characteristics and student self-medication practices. A total of 1,019 students were involved in this study. The most used drugs for self-medication by students were vitamins/multivitamins (91.66%) and analgesics (64.57%). Most medicines used by students were obtained from pharmacies (88.71%), while information related to drugs was obtained from recommendations from friends and family members (72.72%). The primary consideration that prompted students to self-medicate during the COVID-19 era was the easy access to medicines (83.81%). Students' self-medication practices during a health service delivery crisis can be irrational. As this study was conducted within a single institution using a specific sampling approach, the findings should be regarded as context-specific rather than broadly generalizable.